Дано, дуно нимъес уно: Эшлыко чуръес, пиналъеслэн ужъессы / Н. Н. Емельянов - Емельянов Николай Николаевич (2012)
Экземпляры: КО (2013-20) / Инвентарный номер: 50104 / Цена: 100 / Авт.знак: Е 60 / ББК: 82 (2 Рос -Удм)